Contemporary Social Interaction and Misbehavior Among Elementary School Students: Challenges of Character Education in the Digital Era - Suhilmiati, Endhang; Muh. Zuhdy Hamzah; Handayani (PT Inovasi Pratama Internasional, 2026)
The development of digital technology has brought significant changes to the social interaction patterns of elementary school-aged children. Increasing access to digital media, combined with the dynamics of the social environment in rural areas, has given rise to various forms of deviant behavior in elementary school students, such as socializing with older friends, smoking habits, declining ethics and manners, the emergence of intentions to steal other people's belongings, and even bullying behavior among peers. This phenomenon poses a serious challenge for the implementation of character education in the digital era, particularly in the context of elementary education in rural areas such as Glenmore District, Banyuwangi Regency. This study aims to map the trends and directions of scientific studies related to contemporary social interactions, deviant behavior, and character education in elementary school students through a bibliometric approach. The method used is a bibliometric study by searching for scientific articles from reputable databases, such as Scopus, Web of Science, and Google Scholar, over a certain time period. Analysis was conducted on the number of publications, dominant keywords, research theme clusters, and the main actors of the research including authors, institutions, and countries. The results of the analysis indicate that the themes of deviant behavior in children, the influence of the social and digital environment, and character education have become a dominant focus in international and national studies. However, a significant research gap remains regarding contextual studies of elementary school students in rural areas, particularly in Indonesia's rural areas. The implications of this research emphasize the importance of strengthening character education that is adaptive to the challenges of the digital era and based on local contexts, as a foundation for formulating relevant and sustainable character education strategies in Glenmore District, Banyuwangi.